Analisis fluktuasi harga saham “Unusual Market Activity” - Lontokan, Theresia; Mokoagow, Farras Nashirah (Yayasan Widyantara Nawasena Raharja, 2023)
Information is one of the crucial factors in the capital market. This condition tends to be followed by stock price patterns that can experience increases or decreases in the capital market. In early 2023, several issuers obtained UMA status because they were suspected of having unusual share price movements. This study uses 24 issuers that are in conditions of unusual market activity (UMA) as samples. The observation period is January to February 2023 or the period for announcing the UMA status of the issuers being observed. The findings of this study show that the majority of issuers have unusual stock price movement patterns at the 90%, 95%, and 99% confidence levels. However, this study also found that some stock market price patterns tend to be within the confidence range so they tend to be called normal.